Is EU Administrative Law Failing in Some of Its Crucial Tasks?. Issue 5 (September 2016) - Chiti, Edoardo
Abstract: Beneath the surface of steady changes in EU administrative law lurk a number of long‐term, structural problems. In this article, I argue that, because of these structural problems, EU administrative law is failing in some of its crucial tasks: (1) finding a balance between administrative convergence and administrative diversity within the EU legal system, (2) structuring administrative power and its exercise, (3) governing administrative instability. EU administrative law, however, is not necessarily trapped in the status quo. By identifying and articulating a number of long‐term problems, this article aims at providing some tools that future research could use in the discussion on the possible ways forward. More generally, it suggests that EU administrative law should be reshaped as a project of institutional design.